EFFECT OF TAMOXIFEN ON PITUITARY VASOPRESSIN LEVEL - Kundi, Salma Aslam; Forsling, Mary; Kleimestur, Halluck; Wazir, Saleem; Khan, Taj Muhammad (Journal of Ayub Medical College Abbottabad, 2004)
Background: Estrogens modulate the release of Arginine Vasopressin (AVP). There is an increased level of AVP in plasma and pituitary under osterogen hormones. Methods: Ten rats were experimental and ten were controls. The ten experimental rats were injected tamoxifen daily subcutaneously for three days in does of 1 mg/kg body weight in 0.1 ml vegetable oil base. The ten control rats were given 0.1 ml of vegetable oil vehicle only subcutaneously. On the morning of the fourth day all the twenty rats were decapitated. Blood was centrifuged at 2500 rev/min for 15 min at 40C. Plasma was stored at -20oC for assay of AVP. Pituitary gland was removed and homogenized in a test tube containing 1 ml of 0.2 molar acetic acid & stored at -20oC for analysis of pituitary AVP. Uteri of all rats were removed by careful dissection & weighed. Results: Uterine weight and plasma AVP levels were decreased but the pituitary AVP level was unaffected. Conclusion:Under Tamoxifen (anti-estrogen) effect the plasma vasopressin decreased but the level in the posterior was not affected. The effect of osterogen on Hypothalamo Pituitary axis (HPA is measurable in the hypothalamus therefore probably anti-oestrogenic effect would operate more at hypothalamic level rather than posterior pituitary. This needs further investigation at the Hypothalamus level. Key Words: Vasopressin, Tamoxifen, Pituitary